2009
DOI: 10.1109/tps.2009.2033475
|View full text |Cite
|
Sign up to set email alerts
|

Wafer2Wafer Etch Monitor via In Situ QCLAS

Abstract: In this paper, first measurements with a particularly designed quantum-cascade-laser (QCL) arrangement for application in semiconductor industrial environments for in situ wafer-to-wafer etch monitoring are reported. The combination of QCLs and infrared absorption spectroscopy (QCLAS) opens up new possibilities for plasma process monitoring and control. In silicon etch plasmas, concentrations of the etch product SiF 4 were measured real time in an industrial-production environment. The comparison of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Therefore it strongly depends on properties like reactor geometry, flowing conditions, pump speed and the MFC itself. Compared to typical process times for etching deep trench structures in silicon for DRAM production of more than 10min [14], the MFC control via QCLAS in the present configuration would be adaptable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it strongly depends on properties like reactor geometry, flowing conditions, pump speed and the MFC itself. Compared to typical process times for etching deep trench structures in silicon for DRAM production of more than 10min [14], the MFC control via QCLAS in the present configuration would be adaptable.…”
Section: Resultsmentioning
confidence: 99%
“…First applications of an especially designed Q-MACS for in situ process monitoring of the industrial production of DRAMs have been published recently [14]. It was shown, that important etch products, like the SiF 4 molecule, can be monitored in situ during etch processes for deep trench structures in silicon in real-time and under conditions of high volume production.…”
Section: Qclas For Mfc Controlmentioning
confidence: 99%
“…SiF 4 was detected as a key product in such a process using NF 3 , HBr and O 2 as precursor [7,8]. Increasing aspect ratios are ongoing targets in semiconductor industries and require sensitive and reliable monitoring tools and control systems for high volume production processes.…”
Section: Monitoring Of Merie Processes Containing Fluoronitrogenmentioning
confidence: 99%
“…Compared to lead salt diode lasers, distributed feedback (DFB) QCLs provide (i) continuous mode-hop free wavelength tuning, (ii) increasingly high output powers up to hundreds of mW, (iii) near room temperature operation, and in case of cw-DFB-QCLs (iv) narrow line width radiation. Since QCLs offer the possibilities to design very compact and robust spectroscopic instruments, this has stimulated the adaptation of infrared spectroscopic techniques to industrial requirements [7][8][9][10][11][12][13]. Quantum cascade laser absorption spectroscopy (QCLAS) provides a means for determining the absolute concentrations of the ground states of stable and transient molecular species, which is of particular importance for the investigation of reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of applications of QCL based spectrometers as a plasma diagnostic method in the semiconductor industry have been previously published. [20][21][22][23] In this letter, we demonstrate the in situ monitoring of CF 2 radicals using a cw distributed-feedback-QCL (DFB-QCL) operating around 1106.2 cm À1 . It is shown that the monitoring of the CF 2 concentration can serve as a diagnostic tool of dielectric etching plasma processes.…”
mentioning
confidence: 99%